Stationenlernen learning techniques and German language learning outcomes - Samuel Jusuf Litualy; Henderika Serpara (Institute of Advanced Engineering and Science, 2020)
This quasi-experimental study was conducted with the aim of obtaining a clear picture of the presence of influence of the application of Stationenlernen learning techniques to the learning outcomes of German students. The study population was all of these students, while the selected sample was 11th grade students. Data collection techniques used in this study are: (1) observation and interviews, (2) the implementation of pre-test (3) the implementation of experiments, and (4) the implementation of post-test, the data obtained are calculated and analyzed using SPSS -18 to obtain accurate and reliable calculation results. Learning outcomes with Stationenlernen learning techniques turn out to be higher than without it.